ONTOLOGY, EPISTEMOLOGY, AND AXIOLOGY REVIEW FOR CASE BASED BLENDED LEARNING MODEL ASSISTED BY MIND MAPPING TO TEACH STUDENTS CREATIVE SCIENTIFIC IDEAS, COLLABORATION, AND SOCIAL COMMUNICATION - Sari, Dyah Permata; Nursalim, Mochamad; Susarno, Lamijan Hadi (MO.RI Publishing, 2024)
Effective learning requires a deep understanding of the ontology, epistemology, and axiology underlying the learning model used. This article presents a review of the ontology, epistemology, and axiology underlying the Case Based Blended Learning with Mind Mapping (CBBL-MP) Model in the context of teaching students creative scientific ideas, collaboration, and social communication. In this review, we explore the ontological view of reality, epistemological view of knowledge, and axiological view of values and ethics relevant to the application of this learning model. The ontological exploration looks at assumptions about the learning universe, epistemology addresses the sources and validity of knowledge, and axiology highlights the values that are valued in the context of collaborative learning. With a deeper understanding of these foundations, it is expected that the use of the CBBL-MP Model can improve the quality of teaching and learning in developing students' scientific creative ideation, collaboration, and social communication skills.